Japanese Proto-capitalism from the Perspective of Kōjin Karatani’s Theory – a Case Study - Piechnik, Aleksandra (Silva Iaponicarum, 2026)
This paper aims to present the characteristics of the social formation specific to Edo Japan by employing the framework outlined in Kōjin Karatani’s The Structure of World History. Seeing the Tokugawa Era as a proto-capitalist period, the present study applies Karatani’s methodology by contrasting it with available historiographical data and the legacy of the Nihon Shihonshugi Ronsō, a debate heavily relied on by previous research in this area. By using the Mode of Exchange framework, and thus reworking the Marxian architectural metaphor of base and superstructure, Karatani conceptualized a new model of the history of social formations. The main findings indicate that, in the current state of knowledge, it is impossible to duly implement Karatani’s theory to study Japanese proto-capitalism without greater consequences. Nevertheless, the attempt to fit Tokugawa Japan within this framework not only places it within a broader geopolitical discourse and socio-economic reflection but also addresses the status of the theory itself.